Is everyone entitled to health? Screening for Chronic Noncommunicable Diseases in a population without coverage under the Family Health Strategy (Research, Society and Development, 2021)
Objective: To track Chronic Noncommunicable Diseases such as Diabetes Mellitus, Arterial Hypertension and Obesity in a population not covered by the Family Health Strategy. Method: Cross-sectional observational research, with a quantitative approach with primary data. The sample consisted of 62 individuals over 18 years of age, living in a neighborhood located in the rural area of ​​Sarandi-PR. Data were collected by measuring blood pressure, checking capillary blood glucose and surveying anthropometric measurements. The data was tabulated using Microsoft Excel spreadsheets and afterwards a descriptive analysis was performed to characterize the individuals, using the absolute frequency and percentage for categorical variables. Results: Of the research subjects, 74.2% had an altered BMI, 76.0% with a steady partner and 24.0% without. As for cardiovascular risk, 59 (96.7%) were at high risk. The proportion between men and women regarding cardiovascular risks was 1.95: 2. 66.1% of the residents had changes in blood pressure and 29.0% had changes in capillary blood glucose, both fasting and postprandial. Conclusion: It is concluded that the investigated population has a higher prevalence of NCDs compared to the general Brazilian population. Pointing out a need for intervention focused on modifiable behaviors, which can be performed by Primary Health Care through the Family Health Strategy.